The Contributions of Food Groups to the Daily Caloric Intake in Mongolian Population: A Mon-Timeline Study - Oyuntugs Byambasukh (MDPI AG, 2021)
(1) Background: The “Ger Recommendations” have been advised to promote a healthy diet in Mongolia. These recommendations emphasize the ratio of six macro-food components to ensure proper nutrition. In this study, the ratio of these six groups to the total daily caloric intake was determined. (2) Methods: This study was conducted as part of a study at the Clinical Cohort (“Mon-Timeline”) of the Mongolian National University of Medical Science. A macro-community ratio was calculated using a 24-h dietary recall diary of a total of 498 people. (3) Results: The mean age of the study participants was 43.9 ± 12.9 years. Among them, 21.8% (n = 110) were male. Of the total calories, 44.7% were grains, 29.2% were meat and protein products, 9.3% were fats, 7.1% were dairy products, 6.6% were vegetables, and 3.1% were fruits. According to the ratio of the six groups in the Ger Recommendations, meat and grains exceeded the recommended amount, while fruits, milk, and vegetables were consumed less. It has been observed that the older a person ages, the closer they are to following these recommendations. In terms of gender, women consumed more fruit and milk than men. (4) Conclusions: The ratio of macronutrients in the daily caloric intake of Mongolians is inadequate. Therefore, knowledge about the “Ger Recommendations” needs to be studied in relation to people’s healthy eating knowledge and attitudes. If necessary, the appropriate awareness needs to be increased to educate the public on proper eating habits.